The Midas of the Wabash A Biography of John Purdue - Kriebel, Robert C. (Purdue University Press, 2019)
The Midas of the Wabash is a biography of noted businessman John Purdue (1802-1876), whose donations of time and money led to the founding of Indiana's land grant university, Purdue University, in 1869. Purdue also contributed to economically important bridge, railroad, and cemetery construction, the existence of Lafayette Savings Bank and the Battle Ground Collegiate Institute, cattle farming, Lafayette's public school system, and countless other worthy enterprises. This is the first published full length study of Mr. Purdue's life and work beyond casual street-talk that portrayed Purdue as a difficult individual with whom to work. This biography incorporates research efforts by previous writers with facts gleaned from newspaper coverage, official documents, and a few rare samples of Mr. Purdue's letters. In this way, a complete picture of the man and myth is generated.